Early markers of atrial fibrillation recurrence after pulmonary vein isolation - Eva A. H. Lanters; Christophe P. Teuwen; Thijmen Hokken; Sofie Rohde; David B. Haitsma; Felix Zijlstra; Luc J. L. M. Jordaens; Natasja M. S. deGroot (Journal of Arrhythmia, 2020)
Abstract Background Postprocedural atrial extrasystole (AES) frequency predicts atrial fibrillation (AF) recurrence after pulmonary vein isolation (PVI) in patients with paroxysmal AF. However, the predictive value of preprocedural AES frequency is unknown. We investigate whether preprocedural AES frequency is a feasible marker to predict (timing of) AF recurrence after PVI. Methods Patients (N = 684) with paroxysmal or persistent AF undergoing first‐time PVI were evaluated for (a) the frequency of AES/day on Holter recordings without AF prior to PVI, (b) AF episodes during the 90 days blanking period, and (c) AF recurrences afterward. The correlation between AES/day and both development and timing of AF recurrences was tested. Results Preprocedural AES/day was similar in patients with paroxysmal (66 [20‐295] AES/day) and persistent AF (115 [12‐248] AES/day, P = .915). During the blanking period, 302 (44.2%) patients showed AF episodes. AF recurred in 379 (55.4%) patients at 203 (105‐400) days after PVI. AF recurred more frequently in patients with persistent (N = 104 [69.3%]) than in patients with paroxysmal AF (N = 275 [51.5%], P < .001). Frequency of AES prior to PVI was not correlated with development (P = .203) or timing (P = .478) of AF recurrences. AF recurrences occurred both more frequently (P < .001) and earlier (P < .000) in patients with AF during the blanking period. Conclusion AES/day prior to PVI is not correlated with (timing of) AF during the blanking period or AF recurrences, and is therefore not a feasible marker for AF recurrences in patients with PAF. AF during the blanking period is correlated with AF recurrence.